Urban heat island effects on growing seasons and heating and cooling degree days in Madison, Wisconsin USA. (9th February 2016) - Schatz, Jason; Kucharik, Christopher J.
ABSTRACT: Urban areas tend to be warmer than their rural surroundings, a phenomenon known as the urban heat island (UHI) effect. UHIs are nearly always described in terms of temperature. However, UHIs can also be described using derived climate indices, including growing season length, growing degree days (GDDs), and heating and cooling degree days, which may have more direct ecological and economic significance than temperature alone. To characterize UHI effects on these basic climate parameters, we used over 3 years of continuously collected temperature data from up to 150 locations in and around Madison, Wisconsin, USA, an urban area of population 402 000 surrounded by lakes and a rural landscape of agriculture, forests, wetlands, and grasslands. Compared to rural areas, Madison's UHI extended the freeze‐free season by several weeks each year. However, it only shifted the onset of spring and fall (represented by 10‐day moving average temperature crossing seasonal thresholds) by 1 day or less in spring and by a few days to a week in fall. The different effects on freeze dates versus running‐mean temperatures were primarily because the UHI could affect temperatures during individual freeze events much more than it could influence regional seasonal temperature trends. Urban effects on the meteorological growing season were nearly always greater in fall than in spring. We hypothesize that this is due to seasonal differences in sub‐surface temperatures, with urban and rural areas presumably having more uniform sub‐surface temperatures in spring after being frozen throughout the winter, contributing to weaker UHI effects in spring than in fall. In terms of degree days, densely built urban areas averaged 14% (209) more GDDs, 25% (117) more cooling degree days, and 6% (284) fewer heating degree days than rural areas, indicating that the UHI could have significant impacts on energy consumption in Madison.